Investigating the Epidemiology of Mycobacterium bovis Infection in Humans in Ireland. - Mansfield, Mary Elizabeth (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2024)
Mycobacterium bovis is the main cause of bovine tuberculosis. It can cause zoonotic infection in humans. An average of 6 human M. bovis infections are notified annually in Ireland. Little is currently known about the epidemiology of this disease in humans in Ireland. The aim of this study was to (i) investigate the epidemiology of human M. bovis infection in Ireland through review of patients' medical records for host risk factors for infection (ii) perform molecular typing of human M. bovis isolates and compare them with circulating animal M. bovis isolates from cattle and wildlife. Basic demographic details were collected on patients (n=66) who had M. bovis isolates processed at the Irish Mycobacterial Reference Laboratory (IMRL), St James's Hospital (SJH), between 2000 and 2020. A retrospective medical chart review of patients with M. bovis infection who had attended SJH for medical care (n=27) was carried out. Whole genome sequencing (WGS) was performed by the IMRL on 61 human and 3 domestic pet M. bovis isolates recovered by, or referred to, the IMRL between 2000 and 2020. Human M. bovis genomic sequence data was compared with sequence data from 123 Irish animal M. bovis isolates collected by the School of Veterinary Medicine at University College Dublin (n=45) and the Department of Agriculture, Food and the Marine (n=78) from infected cattle and wildlife. Core genome multilocus sequence typing (cgMLST) was used to create minimum spanning trees and to identify 'clusters'. Cluster threshold was set as < 12 allelic differences between isolates. Where clusters were identified by cgMLST, further single nucleotide polymorphism (SNP) analysis was performed on each cluster using the bioinformatic pipeline MTBseq. Sixty-two percent of patients with M. bovis infection were male, average age at diagnosis was 50.1 years. Where disease site was recorded (n=57), pulmonary infection occurred in 71.4%, extrapulmonary disease in 14.2%. and disseminated disease in 14.2%. Frequent comorbidities, where recorded (n=22), included HIV infection (n=3), malignancy (n=4) and autoimmune conditions (n=7). Four patients were receiving biologic immunosuppressants. The most recorded occupations were farmer (n=5) and meat factory worker (n=5). Among the 61 human and 3 domestic pet M. bovis isolates sequenced by the IMRL and the 123 externally derived animal isolates, cgMLST identified 20clusters involving 37 patients, 3 domestic pets and 60 animal isolates. Seventeen of these clusters contained one or more human M. bovis isolates. Fourteen clusters contained both human and animal isolates. Subsequent whole genome SNP analysis performed on these clusters showed that 1 cluster involved patient isolates (n=2) that were <6 SNPs apart from each other, suggestive of close epidemiological link. One cluster found multiple patients (n=7) had M. bovis isolates that were less than 6 SNPs apart from circulating animal isolates, including a domestic pet isolate, again suggestive of close epidemiological links. This study highlights the changing epidemiology of human M. bovis infection. It also demonstrates that there is likely ongoing transmission of M. bovis between animals, between animals (including domestic pets) and humans, and potentially between humans. Prospective studies are needed in this area to further understand the epidemiological links between animal and human cases of M. bovis infection.
APPROVED
Keywords: Tuberculosis; One Health; Mycobacterium bovis; Bovine Tuberculosis; Whole Genome Sequencing; Zoonotic